2006
DOI: 10.1093/nar/gkj086
|View full text |Cite
|
Sign up to set email alerts
|

The Zebrafish Information Network: the zebrafish model organism database

Abstract: ABSTRACT10 The Zebrafish Information Network (ZFIN; http://zfin. org) is a web based community resource that implements the curation of zebrafish genetic, genomic and developmental data. ZFIN provides an integrated representation of mutants, genes, genetic markers, 15 mapping panels, publications and community resources such as meeting announcements and contact information. Recent enhancements to ZFIN include (i) comprehensive curation of gene expression data from the literature and from directly sub-20 mitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
202
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(209 citation statements)
references
References 3 publications
(2 reference statements)
7
202
0
Order By: Relevance
“…The approach was informed by a number of considerations including (i) the selection of developmental stages that will likely be screened for dysregulated protein expression in large scale mutagenesis or chemical screens, (ii) the simplicity of sample preparation and analytical methodology (mindful of their possible adaptation to high throughput screening), (iii) the eminent quality of mass spectrometric protein identifications, (iv) the accessibility of the protein data in a fully searchable database and their integration with existing genomics and genetics resources provided to the zebrafish research community through the ZFIN database (32), and (v) the comprehensive categorization of proteins by functional classes to facilitate the selection of candidate proteins, for example for the design of targeted quantitative mass spectrometry assays (29). Our approach yielded 1384 unique proteins at 72 or 120 hpf by 2D LC-ESI-MS/MS and 477 unique proteins at 72 or 120 hpf by 2D PAGE-MALDI-TOF/TOF, which showed an overlap of about 30%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach was informed by a number of considerations including (i) the selection of developmental stages that will likely be screened for dysregulated protein expression in large scale mutagenesis or chemical screens, (ii) the simplicity of sample preparation and analytical methodology (mindful of their possible adaptation to high throughput screening), (iii) the eminent quality of mass spectrometric protein identifications, (iv) the accessibility of the protein data in a fully searchable database and their integration with existing genomics and genetics resources provided to the zebrafish research community through the ZFIN database (32), and (v) the comprehensive categorization of proteins by functional classes to facilitate the selection of candidate proteins, for example for the design of targeted quantitative mass spectrometry assays (29). Our approach yielded 1384 unique proteins at 72 or 120 hpf by 2D LC-ESI-MS/MS and 477 unique proteins at 72 or 120 hpf by 2D PAGE-MALDI-TOF/TOF, which showed an overlap of about 30%.…”
Section: Discussionmentioning
confidence: 99%
“…The data are accessible on line in a fully searchable database that links protein identifications to existing resources including the ZFIN database (32). This new resource should allow the selection of candidate proteins for targeted quantitation (29) in mutagenesis and chemical screens and may refine systematic genetic network analysis in vertebrate development and biology.…”
Section: Fig 1 Estimated Sensitivity and Error Of Protein Identificmentioning
confidence: 99%
“…Mosaic gene expression is a hallmark of embryonic development in notably mouse (Rossant and Tam, 2009) and zebrafish (Sprague et al, 2003;Lunde et al, 2004;Sprague et al, 2006) and may be at the origin of lineage specification. Whole-mount in situ hybridization of MBT + embryos showed that sox3 was ubiquitously expressed (Fig.…”
Section: Mosaic Klf4 Expression In Embryos Correlates With Co-detectimentioning
confidence: 99%
“…Based on genome-wide data from mouse and human embryonic stem cells (Azuara et al, 2006;Bernstein et al, 2006;Pan et al, 2007), as well as in hematopoietic progenitors (Cui et al, 2009), such H3K4/K27me3 "bivalent" state would predict that non-klf4 expressing cells are programmed for later upregulation of the gene. Indeed, klf4 is strongly upregulated post-MBT (Sprague et al, 2003;Sprague et al, 2006;O'Boyle et al, 2007). Interestingly, recent genome-wide H3K4me3 and H3K27me3 promoter mapping data in mouse embryos reveals co-enrichment of these marks on developmentally-regulated genes (Dahl et al, 2010).…”
Section: Epigenetic States Of Embryonic Genes In Relation To Developmmentioning
confidence: 99%
“…Zebrafish have surged in importance as an animal model in almost every field of medicine, [9][10][11] owing to their publicly available genomic sequence, 12 their external fertilization, rapid development, accessibility of embryos (larvae) and the evolutionary conservation of the vertebrate body plan. Their precocious development of vision and remarkable evolutionary conservation of the eye make the zebrafish retina an excellent model for human visual disorders.…”
Section: Introductionmentioning
confidence: 99%